Forage evaluation in ruminant nutrition [ - Givens, D. I. [ (D. Ian)] (CABI, 2000)
Pressures to maximize the use of forages in ruminant diets have renewed interest in fast, inexpensive methods for the estimation of their nutritional value. This book addresses the status of these procedures, and their potential and limitations.